UJI EFEK ANTIINFLAMASI KOMBINASI EKSTRAK ETANOL DAUN GYMNANTHEMUM AMYGDALINUM DEL. DAN ELAEIS GUINEENSIS JACQ. - Wahyudi, Wahyudi; Masnawati, Masnawati; ., Ismayuni; Rahmi, Sofia; Berkat Waruwu, Syukur (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2020)
Inflammation is a response from the body to injury or infection, flavonoids contained in African leaves (Gymnanthemum Amygdalinum Del.) And palm oil leaves (Elaeis Guineensis Jacq.) have anti-inflammatory effects. This study aims to examine the anti-inflammatory effects of a combination of ethanol extracts of Gymnanthemum Amygdalinum Del. And Elaeis Guineensis Jacq. on white rat foot edema which is induced by carrageenan 1% subplantar, and effective dosage as anti-inflammatory. The extract was made by maceration method using 96% ethanol solvent. The antiinflammatory effect test was divided into 5 treatment groups. The first group (negative control) was given 0.5% CMC Na suspension, the group (positive control) was given diclofenac Na suspension 2.25 mg / kg bw, and the suspension group was a combination of African leaf extract (Gymnanthemum Amygdalinum Del.) And palm oil leaves ( Elaeis Guineensis Jacq.) Dose 200 + 62.5 mg / kg bw, 400 + 125 mg / kg bw, and 800 + 250 mg / kg bw. Inflammation volume measurements were measured using a pletismometer for 180 minutes at 30 minute intervals after 1% carrageenan was induced. The results showed that negative controls had significant differences with other treatment groups which did not show anti-inflammatory effects. In conclusion, the suspension of a combination of ethanol extract of African leaves and palm oil leaves has an effective anti-inflammatory effect at a dose of 800 + 250 mg / kg bw.